1993
DOI: 10.1016/0378-1097(93)90324-u
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of the ?-ribulose-1,5-bisphosphate carboxylase/oxygenase form II gene from Thiobacillus intermedius in Escherichia coli

Abstract: Both form I and II ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO) genes were detected in Thiobacillus intermedius by heterologous hybridization using specific probes from Anacystis nidulans and Rhodobacter sphaeroides, respectively. However, only the previously reported form I enzyme could be demonstrated in cells grown under a number of different conditions. The reason(s) why the form II gene is not expressed in T. intermedius is/are not clear at this time. The form II gene was isolated from a lamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…This has been shown previously for other SOB species, such as Acidithiobacillus ferrooxidans, Thiobacillus sp. (English et al, 1992), Halothiobacillus neapolitanus (Baker et al, 1998), Thiomonas intermedia (Stoner & Shively, 1993) and Thiomicrospira sp. (Tourova et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown previously for other SOB species, such as Acidithiobacillus ferrooxidans, Thiobacillus sp. (English et al, 1992), Halothiobacillus neapolitanus (Baker et al, 1998), Thiomonas intermedia (Stoner & Shively, 1993) and Thiomicrospira sp. (Tourova et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Cupriavidus necator H16 (formerly Alcaligenes eutrophus H16) possesses two sets of almost identical genes which encode the red-like form I enzyme (Kusian et al, 1995), Allochromatium vinosum (formerly Chromatium vinosum) has two sets of divergent genes which encode the green-like form I enzyme (Viale et al, 1989) and Rhodobacter azotoformans has two sets of genes which encode both green-and red-like form I enzymes (Uchino & Yokota, 2003). Furthermore, Halothiobacillus neapolitanus (formerly Thiobacillus neapolitanus), Thiomonas intermedia (formerly Thiobacillus intermedius), Thiobacillus denitrificans, Rhodobacter sphaeroides and Rhodobacter capsulatus have genes for both form I and form II enzymes (Gibson & Tabita, 1977a, b;Shively et al, 1986;English et al, 1992;Stoner & Shively, 1993;Paoli et al, 1995). Acidithiobacillus ferrooxidans (formerly Thiobacillus ferrooxidans) and Hydrogenovibrio marinus have three different sets of RubisCO genes, two encoding the green-like form I enzyme, whereas the third one encodes a form II enzyme (Kusano et al, 1991;Heinhorst et al, 2002;Yaguchi et al, 1994;Nishihara et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…intermedia K12 Sau3A-lambda library with the cbbL gene from A. nidulans resulted in the isolation of three positive clones designated Ti102, Ti104, and Ti108 [27,28]. Probing these clones with the csoS1 gene of H. neapolitanus demonstrated that Ti102 and Ti108, but not Ti104, contained at least parts of both cbbL and csoS1 genes (unpublished).…”
mentioning
confidence: 99%